Mendoza the Jew : boxing, manliness, and nationalism : a graphic history - Schechter, Ronald; Clarke, Liz 1982- (Oxford University Press, 2014)
"Mendoza the Jew combines graphic history with primary documentation and contextual information to analyze and explore issues of nationalism, identity, culture, and historical methodology through the life story of Daniel Mendoza, a poor Sephardic Jew from East London who became the boxing champion of Britain in 1789"--